Characterization of acid-modified corn cob biochar for potential alkaline soil remediation - MAHMOUD A. M. HASSAN; MOHAMED E. A. EL-SAYED; MOHAMED H. ABDALLAH; AHMED A. GAHLAN (Smujo International, 2026)
Abstract. Hassan MAM, El-Sayed MEA, Abdallah MH, Gahlan AA. 2026. Characterization of acid-modified corn cob biochar for potential alkaline soil remediation. Asian J Agric 10 (1): g100125. https://doi.org/10.13057/asianjagric/g100125. Biochar (BC), derived from agricultural residues, is increasingly recognized for its capacity to enhance soil quality and contribute to the reduction of greenhouse gas emissions. Conversely, the typically high pH of BC limits its effectiveness in alkaline soils, such as those prevalent in Egypt. In order to overcome this difficulty, this study produced BC from corncobs via slow pyrolysis at 350°C for an hour at a heating rate of 10°C min-1. Its surface was modified with phosphoric acid, sulfuric acid, and humic acid, resulting in PBC, SBC, and HBC, respectively. Biochar and its modified forms were characterized by elemental analysis, Fourier Transform Infrared (FTIR) spectroscopy, X-Ray Diffraction (XRD), Brunauer-Emmett-Teller (BET) surface area, and Field-Emission Scanning Electron Microscopy (FE-SEM). The findings revealed that the pH of MBCs has decreased from 7.87 to 7.13 compared to 8.32 for BC. This adjustment can improve the compatibility of BC with alkaline soils. In addition, all Modified Biochars (MBCs) have higher surface areas of 83.73, 79.60, and 75.23 m²/g for HBC, SBC, and PBC, respectively, compared to 73.41 m²/g for unmodified BC. Pores of MBCs were microporous, while BC is composed of mesopores. The elemental analysis demonstrated that the MBCs have more functional groups than BC, which improves BC properties and applications. Overall, the MBCs demonstrated enhanced specific physicochemical properties, particularly in pH adjustment, functional groups, surface areas, and pore size distribution following the order: HBC>SBC>PBC>BC, suggesting their potential as effective ameliorants for alkaline soils. These results highlight the benefits of agricultural waste and tailoring BC properties to address the specific needs of alkaline soils, while also contributing incidentally to carbon sequestration as a beneficial secondary outcome.